Determination of Selenium in Milk by Graphite Furnace Atomic Absorption Spectrometry - Vongkul, A.; Dejmanee, S. (Asian Journal of Chemistry, 2013)
This work has optimized the graphite furnace atomic absorption spectrometry to directly determine the total selenium concentrations in milk samples. The study emphasized the effect of modifiers on the sensitivities and stabilizations of three selenium species (selenomethionine, selenite and selenate) that were spiked in aqueous solution and diluted milk solutions. At the same time, palladium nitrate, rhodium chloride and the combinations of these modifiers with magnesium nitrate were used as chemical modifiers. The use of a combination between 5 μg Pd(NO3)2 and 3 μg Mg(NO3)2 was successful modifier in an equal sensitivities and stabilization for all these species in both aqueous and milk solutions. This modifier can be applied for the direct determination of selenium in milk samples with standard addition method. The Se content in milk samples was found range from 33 to 70 μg L-1. The percentage recovery was found within the range between 87.42 to 111.69 %.